An Analysis of the Literacy Activities Provided by Preschool Teachers - Tolga ERDOĞAN; Şenay ÖZEN ALTINKAYNAK; Özge ERDOĞAN (Elementary Education Online, 2023)
The aim of the study is to analyze the views of preschool teachers’ about literacy activities. In order to identify which literacy activities are used by the teachers, semi-structured interviews were carried out. The findings of the study indicate that preschool teachers participated in the study sufficiently give place in their instruction to the activities towards the development of the writing skill. However, it is also found that the activities in regard to the development of skills such as phonological awareness, visual perception, vocabulary, listening and speaking are very limitedly employed and when employed, such activities occur in a limited fashion in terms of variety.